Understanding phosphorus dynamics in wheat plant and growth response in a split-root system in acidic soil - Shabnam, Rubya; Tarek, Mehedi Hasan; Iqbal, Md Toufiq (Agriculture and Natural Resources, 2018)
Phosphorus (P) is an essential nutrient for plant growth since it is involved in cellular energy transfer, respiration, and photosynthesis. The P status and P distribution were examined in different parts of the wheat (Triticum aestivum) plant and root and shoot growth response in a split-root soil culture in acidic soil (pH 5.2), collected from the acidic region of Bangladesh. KH2PO4 was used as the source of P for the different levels of P application. Two recently developed wheat varieties (BARI-GOM 25 and BARI-GOM 26) were used as testing plants with three replications. The results showed that growth parameters like plant biomass increased by up to 80% over the control P application. Likewise, P uptake by wheat seedlings also increased by up to more than 8 times compared with the control P application. However, no significant differences were observed between wheat varieties irrespective of growth and P uptake by the wheat seedlings. Moreover, elevated P concentrations in the shoot of wheat plants probably provided more P for shoot unloading of P and for P assimilation in the control roots, resulting in increased P concentrations in the roots of wheat plants that indicated the translocation of P in the roots. These findings indicated that added soluble P increased the absorption of nutrients under acidic soil conditions. However, application of elevated P is efficient for both increasing shoot development and root growth and plays a significant role in the phosphorus dynamics within wheat plants in a split-root system.